Design and Construction of a Smart Mini Greenhouse for Pak Choy Plants - Ayendra Asmuti; Rahmi Awalina (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This research aims to design and develop a “Smart Greenhouse” system that optimizes environmental conditions to maximize yield, enhance product quality, and enable precise production scheduling. These findings serve as a foundational reference for engineering microclimates and automated production systems, specifically for Pak Choy. While the prototype generally operated as intended, the light intensity and temperature did not consistently meet target indicators, requiring further refinement. Furthermore, plant growth was non-uniform due to uneven light distribution and a unidirectional nutrient flow system. To reach commercial viability, future development must focus on optimizing these environmental variables to better align with specific plant characteristics. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action